2018
DOI: 10.1002/ppap.201800083
|View full text |Cite
|
Sign up to set email alerts
|

Young's modulus of plasma‐polymerized allylamine films using micromechanical cantilever sensor and laser‐based surface acoustic wave techniques

Abstract: Mechanical properties of ultra‐thin organic films are fundamentally important in coating applications. Micromechanical cantilever sensor (MCS) and laser‐based surface acoustic wave (LA‐SAW) techniques were both used to measure Young's moduli (E) of plasma polymerized films at different humidities (H). For plasma polymerized allylamine (ppAA) films deposited at 5 W and 90 W, E of 1400 ± 350 MPa and 110 ± 20 MPa at H between 10 and 40%, and 1070 ± 250 MPa and 32 ± 10 MPa at H between 70 and 80% were measured. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Good examples of the common trend mentioned before in which increasing input power results on higher elastic modulus can be found in literature [26,34]. In addition, as tribological and mechanical properties are closely related, some tribology results showed to follow a similar behavior.…”
Section: Input Power: a Parameter For Continuous Wave Plasma Polymerizationsupporting
confidence: 60%
See 2 more Smart Citations
“…Good examples of the common trend mentioned before in which increasing input power results on higher elastic modulus can be found in literature [26,34]. In addition, as tribological and mechanical properties are closely related, some tribology results showed to follow a similar behavior.…”
Section: Input Power: a Parameter For Continuous Wave Plasma Polymerizationsupporting
confidence: 60%
“…More recently, Toda et al [34] measured the Young's modulus of plasma polymerized allylamine films through micromechanical cantilever sensor and laser-based surface acoustic wave techniques. The authors observed that smaller Young's modulus values were obtained with surface acoustic waves technique when compared to the micromechanical cantilever sensor.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the Young’s modulus of a 55 nm polyethylene membrane was estimated at 10 GPa [ 27 ], that of carbon nanomembranes of 1 nm thickness was reported to be 45 GPa [ 28 ], that of a vapor-deposited, 30 nm tris(8-hydroxyquinoline) aluminum film was 2.81–3.88 GPa [ 29 ], and that of 320 nm Si membrane was 220 GPa [ 30 ]. One of the lowest Young’s modulus values (32 MPa) was reported for ~100 nm plasma-polymerized allylamine films [ 31 ], but even this value is more than an order of magnitude higher than that for the PEG membranes.…”
Section: Resultsmentioning
confidence: 98%
“…Such surface stress measurement based on the bending might not be effective because of the energy loss for bending in the vertical direction and for slipping in the lateral direction due to the low bonding strengths at the interface between the Si surface and absorber material [15]. In addition, the vertical swelling of one-side free film causes an extra low Young's modulus of absorber during swelling and results in lower surface stress changes applied to sensors [16]. In order to more efficiently transduce the swelling effect of the absorber to strain in the piezoresistive element and, therefore, achieve higher sensitivity, we embed the absorber in the sensor.…”
Section: Introductionmentioning
confidence: 99%